2008
DOI: 10.1007/s00417-008-0805-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-arteritic anterior ischemic optic neuropathy: role of systemic corticosteroid therapy

Abstract: This study suggested that NA-AION eyes treated during the acute phase with systemic corticosteroids resulted in a significantly higher probability of improvement in visual acuity (p = 0.001) and visual field (p = 0.005) than in the untreated group. Both visual acuity and visual fields improved up to 6 months after onset of NA-AION.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(124 citation statements)
references
References 39 publications
3
114
0
7
Order By: Relevance
“…The use of steroids is controversial, with some studies showing a positive outcome. 3,22,23 The use of combined levodopa and carbidopa has been found to improve visual acuity in patients with AION. 24 In addition, significant improvement in vision has been reported with steroids and levodopa.…”
Section: Case Reportmentioning
confidence: 99%
“…The use of steroids is controversial, with some studies showing a positive outcome. 3,22,23 The use of combined levodopa and carbidopa has been found to improve visual acuity in patients with AION. 24 In addition, significant improvement in vision has been reported with steroids and levodopa.…”
Section: Case Reportmentioning
confidence: 99%
“…At the time of NA-AION onset in this patient, no effective therapy for NA-AION was available [9,10]. Meanwhile, promising data on the beneficial effect of systemic corticosteroids on visual acuity and visual field improvement in the treatment of NA-AION have been published, and represent the only proven beneficial therapy option [11,12].…”
Section: Discussionmentioning
confidence: 91%
“…At the time of diagnosis of NA-AION in this patient and start of treatment with brimonidine (Alphagan®) no treatment for NA-AION had been proven beneficial. Reports about beneficial effect of systemically administered corticosteroids were not yet available [12].…”
Section: Case Reportmentioning
confidence: 99%
“…Few studies [25] [26] in literature concluded role of oral steroids in improvement of visual acuity and fields but results were not accepted due to non-randomization, small sample size, selection bias. No studies have documented role of intravenous steroids.…”
Section: Medical Treatmentmentioning
confidence: 99%